2022
DOI: 10.4103/jfmpc.jfmpc_1193_22
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in diabetic patients; prevalence, correlates, and moderating effect in Taif, Saudi Arabia

Abstract: A BSTRACT Background: Diabetes is associated with a range of psychosocial stressors that could lead to considerable distress and increased risk of depressive symptoms. There is a pressing need to understand the underpinnings of diabetes-related distress and how it evolves in connection with depressive moods, and fears related to hypoglycaemia. Our current study attempts to fill this knowledge gap and further explore the interconnections between distress, fear, and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“… 22 The longer a person has diabetes, the more likely they are to experience psychological complications, such as depression. 23 Moreover, the demand for efforts to educate the general population about the complications of diabetic neuropathy has also been reported in India and Malaysia. 24 Increasing caregivers’ knowledge about these complications is important in decreasing their incidence.…”
Section: Discussionmentioning
confidence: 99%
“… 22 The longer a person has diabetes, the more likely they are to experience psychological complications, such as depression. 23 Moreover, the demand for efforts to educate the general population about the complications of diabetic neuropathy has also been reported in India and Malaysia. 24 Increasing caregivers’ knowledge about these complications is important in decreasing their incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The term "Health Related QoL" (HRQoL), the self-perceived health status, is often used interchangeably with QoL, and it consists of three broad domains: physical, psychological, and social functioning [7]. Research has shown that living with a chronic illness, including cardiovascular disease [8,9], various types of cancer [10][11][12][13][14], stroke [15,16], and diabetes [17][18][19] can be significantly challenging for many aspects of QoL [20].…”
Section: Introductionmentioning
confidence: 99%